Police diversity and crime clearance for Black and Hispanic victims - Roberts, Aki (Criminology & public policy, 2023)
Research Summary As a policy response to historically strained police-minority community relations, police diversification is hoped to improve policing outcomes in minority communities. An improved police-community relationship may be expected to lead to increased citizen cooperation in crime investigations and therefore be beneficial for crime clearance, but there are different perspectives on the nature of this link. We examined several measures of Black police representation (Black officer percentage, Black racial congruence between the police force and the jurisdiction's population, and presence of Black police chief or head) and their relationships with arrest clearance of National Incident-Based Reporting System aggravated assault incidents involving Black victims in 205 agencies. We also explored similar Hispanic police representation measures in a sample of aggravated assault incidents with Hispanic victims in 158 agencies. In multilevel survival analyses with agency/jurisdiction- and incident-level controls, none of the Black representation measures were significantly associated with clearance of Black victims’ incidents. We obtained similar results for the Hispanic representation measures and clearance of Hispanic victims’ incidents. Policy Implications Although the findings do not indicate a benefit of diversity for clearance involving minority victims, it is encouraging that neither do results suggest that increasing minority police representation would harm clearance. Responding to the public's strong call for demographic reform, it appears that police agencies can continue to increase their racial and ethnic diversity without sacrificing clearance rates, a main indicator of police performance. At least for clearance, warnings of reduced performance when equitable representation is an agency priority do not seem to be well-founded. There should be continuing research on policing outcomes and diversity as U.S. agencies increase their minority representation, and agencies should emphasize the recruitment, hiring, and retention of minority officers.